(3eNJUQ cJGH GdRQObI aj GdNjd hCeQGVgG heG jJYdb HgGs - (3eMeO Hf YHO Gddg GdeYQha HdSGf GdOjf Hf GdNWjHs
(3ChdgG (B:s
(3hgh CHhGH cKjQI GbJUQfG efg Ydi ahGFO EPG LYdJ ai CYfGb GdNjd NQRkG UfYJg ef bQhf GdCjGFd CefJ ef GdYjf bdgG bhe ef Cgd GdeYQaI EPG CQOJ s
(3BNQgG (B:s
(3Ke jPQg Ydi GdJhJI KdGKI GjGe , aEPG GfbdYJ aOb YUaI hbTQ QeGf (B( (3aGFOI dMaX GdWYGe (B) (3hVY gPG GdWYGe Ch gPg GdeHQI ai MaQg agi GdeWeheQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B226 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs